Datacenter power and energy management: past, present, and future - Bianchini, Ricardo; Christian Belady; Sivasubramaniam, Anand (IEEE Micro, 2024)
This article overviews some of the key past developments in cloud datacenter power and energy management, where we are today, and what the future could be. This topic is gaining enormous, renewed interest in the context of the conflicting needs of the AI revolution and the climate crisis.